Application of TALYS code for Calculation of Fission Cross Section and Fission Yield of Several Heavy Nuclides - Yuda S. Perkasa; Rizal Kurniadi; Abdul Waris (Institut Teknologi Bandung, 2009)
Nuclear data evaluation for fission cross section and fission yield had been performed by many investigators using different models of approximation theoretically. These models are encapsulated and implemented into computer codes to perform more robust nuclear reaction data calculations. TALYS is one of most successful nuclear reaction codes that used to determine fission cross section and fission yield. In this paper, TALYS code was used to calculate some fission reaction including Am-241 (n,f), Th-232 (n,f), and U-235 (n,f). These calculations are performed using different set of reaction mechanism and optical model parameter adjustment, such as fission barrier parameter, level density parameter, transmission mechanism, and so on. Reaction mechanism and parameter adjustment are selected based on reaction characteristics to obtain more accurate and reasonable result. The accuracy of calculation result are heavily depend on the reaction mechanism selection and parameter adjustment. All obtained results have been compared with ENDF nuclear data library.